Decolorization of Acacia Seyal Gum Arabic (University of Khartoum Engineering Journal, 2022)
This work aimed to decolourization of Acacia Seyal (Talha) Gum Arabic to improve its quality. Theexperimental set up consists of adsorption column made of Perspex. The adsorption media is activated charcoal of350 m pore size. The adsorption bed is 15 cm in depth and 3.5 cm in diameter. The experiment is conducted forwide range of Talha Gum concentrations (5.5 -55 g/L). The transmittance is measured for wide range of wavelength (350 to 800 nm). The result showed that the colour has changed from pink to colourless-transparent. Thetransmittance (%) has improved by 5 to 22% depending on the initial transmittance. The colour removal is foundto have significant influence on pH, and total dissolved solid (TDS) and less influence on viscosity. The pHincreased by 1 unit indicating that the impurities are of basic origin. The TDS is reduced by 20 to 50% indicatingthe removal of other salts excluding Ca+2 and Mg+2 ions.